Legalitas Pendirian Yayasan Oleh Orang Asing Di Indonesia - Muhamad Khamal Akbar Rahmadan; I Made Sarjana (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
The research was conducted for the sole purpose of knowing the legality of establishing a foundation as a legal entity operating in the social, religious, and humanitarian fields, in this case the foundation was founded by foreigners. This research uses a method with normative research in addition to legislation is used as an approach, in addition to facts and conceptual analysis used as an approach in this research method. The results of the study indicate that the legali ty of the establishment of a foundation by foreigners in Indonesia has now been determined in Law Number 28 of 2004 concerning Amendments to Law Number 16 of 2001 concerning Foundations where foreigners in this context have more opportunities to set up a foundation. Regulations on foreign foundations are related to their establishment which are further emphasized in Government Regulation Number 63 of 2008 concerning the Implementation of the Law on Foundations as an implementing regulation that provides legal certainty to foreigners in establishing a foundation. as well as the nation, and the State of Indonesia.